Policies and Practice of Force in Nigerian Policing: A Case Study of Yelwa Division Bauchi Police Command - Uwais, Idrees Abdullahi; Shehu, Ibrahim Adamu; Maijama'a, Maryam Sanusi; Gwani, Abdullatif Isa; Sulaiman, Usman Muhammad (Darul Yasin Al Sys, 2025)
This study aims to evaluate the policies and practice of force in Nigerian policing in yelwa division Bauchi Police command. The research objectives: know the mechanisms in existing policies that police use for mitigating excessive force, analyze the impact of police accountability mechanisms on public trust and community relations, evaluate the effectiveness of existing policies that police use in mitigating incidents of excessive force, assess the influence of training in de-escalation techniques and to access the implicit bias recognition on police officers' use of force in Yelwa division Bauchi Police command. This study employed survey research technique and developed a set of structured questionnaire as instrument utilized in collecting primary data. The data was analyzed using descriptive and inferential statistical techniques to provide a comprehensive overview of the respondents' perceptions and experiences. The findings indicate that majority of respondents believe that these mechanisms have increased trust and improved community relations, though some still report no change or a decrease in trust, respondents generally perceive existing policies as moderately effective in reducing excessive force, there is room for improvement. The study concludes that current policies require enhancement to improve their effectiveness in addressing excessive force. It recommended that regular policy reviews, improved community engagement, and enhanced transparency in accountability mechanisms. Additionally, it suggests the implementation of continuous training programs to better support officers in de-escalation and bias recognition. Limitations include a small sample size and variability in respondents' perceptions, which underscores the need for further research with a larger and more diverse sample to validate and expand upon these findings.